Numerical prediction of vortex-induced vibration of flexible riser with thick strip method. (August 2019) - Bao, Y.; Zhu, H.B.; Huan, P.; Wang, R.; Zhou, D.; Han, Z.L.; Palacios, R.; Graham, M.; Sherwin, S.
Abstract: We present numerical prediction results of vortex-induced vibration (VIV) of a long flexible tensioned riser subject to uniform currents. The VIV model of long length-to-diameter ratio is considered and 'thick' strip technique based on high-order spectral/ hp element method is employed for computational simulation. The model parameter of the riser for the simulation is chosen according to the dimensional counterparts used in the experimental tests in Lehn (2003). The numerical results are displayed in terms of motion responses, hydrodynamic forces and wake patterns as well and compared and discussed with the available data in the literature.